2010
DOI: 10.1021/es9025529
|View full text |Cite
|
Sign up to set email alerts
|

Greenhouse Gas Emissions Driven by the Transportation of Goods Associated with French Consumption

Abstract: The transportation of goods plays a significant role in the overall greenhouse gas emissions from consumption. This study investigates the connections between French household consumption and production and transportation-related emissions throughout product supply chains. Here a two-region, environmentally extended input-output model is combined with a novel detailed, physical-unit transportation model to examine the connection between product, location of production, choice of transport mode, and greenhouse … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 16 publications
2
10
0
Order By: Relevance
“…They claim that the primary advantage of IOM is that it provides a standard method of analysis that can be updated or applied to different populations in a uniform manner. Several subsequent papers employ this technique in calculating the carbon emissions of particular products or services in countries such as France (Hawkins and Dente, 2010) and Norway (Larsen and Hertwich, 2011). Based on this original model, other developed models include the United Kingdom Quasi-Multi-Regional InputeOutput (QMRIO) models Jackson, 2009, 2010) and the Norwegian Environmentally Expanded InputeOutput models (Larsen and Hertwich, 2011) to widen the scope.…”
Section: Input-output Model (Iom)mentioning
confidence: 99%
“…They claim that the primary advantage of IOM is that it provides a standard method of analysis that can be updated or applied to different populations in a uniform manner. Several subsequent papers employ this technique in calculating the carbon emissions of particular products or services in countries such as France (Hawkins and Dente, 2010) and Norway (Larsen and Hertwich, 2011). Based on this original model, other developed models include the United Kingdom Quasi-Multi-Regional InputeOutput (QMRIO) models Jackson, 2009, 2010) and the Norwegian Environmentally Expanded InputeOutput models (Larsen and Hertwich, 2011) to widen the scope.…”
Section: Input-output Model (Iom)mentioning
confidence: 99%
“…Weber and Matthews (2008) and Hawkins and Dente (2010) found that, in general, carbon emissions from transporting agricultural products represent 0.5 % of total greenhouse gas emissions. This number correlates to the results of system 1.…”
Section: Transportmentioning
confidence: 99%
“…Changes towards a healthier diet, decreasing the intake of meat and dairy, and increasing vegetables, fruits and cereals (Weber and Matthews, 2008;Cazcarro et al, 2012), local sources of food (Weber and Matthews, 2008;Hawkins and Dente, 2010), seasonal fruit and vegetable products, homemade, publicly catered and ready-to-eat dishes (Virtanen, 2011) or less elaborated food products, have an effect on generated greenhouse gases. However, the articles quoted above have conducted limited analysis of the agricultural sector despite using LCA-IO models.…”
Section: A N U S C R I P Tmentioning
confidence: 99%
“…Increases in carbon footprints are also due to a growing number of goods traveling thousands of kilometers for final consumption or as inputs in several production processes along the way (Cadarso et al, 2010;Cristea et al, 2013 andVöhringer et al, 2013). Agricultural products are experiencing the same phenomenon, as conveyed in the concept of foodmiles by domestic (Nealer et al, 2012) and international agricultural products (Weber and Matthews, 2008 1 ;Hawkins and Dente, 2010). Through the concept of food-miles, emissions linked to food production processes and emissions from food long-distance transportation and distribution are calculated and compared and the last ones represent around 15% of the first (Weber and Matthews, 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation